TYPICAL ENDOMETROID ADENOCARCINOMA OF OVARY IN A YOUNG WOMAN- A RARE CASE - DR SUNITA SAMAL,; DR SHWETA GUPTA,; DR AKSHAYA MAHAPATRA,; DR P.PORKKODI, (International Journal of Pharma and Bio Sciences, 2015)
Endometroid adenocarcinoma of ovary accounts for less than 10% of all surface epithelial tumors and usually involves 5th to 7th decades of life. A 27yr unmarried woman was presented with an abdominal mass and both clinical and sonological evaluation revealed a 20wk size solid ovarian mass in one ovary. All the tumor markers were within normal values. She had undergone laparotomy which showed stage1a ovarian tumor and unilateral salpingo-oopherectomy with omental biopsy was done. Histopathology diagnosed it as a well differentiated endomatroid adenocarcinoma of ovary without any metastasis.